Assessment of Mothers’ Knowledge of the Health Benefits of Olive Oil in Benghazi, Libya - Ahamdi, Ibtisam M.; Abuaziza, Fatma B.; Khalifa, Massoudah O.; Ahmadi, Antesar Mohamed (Sebha University Conference Proceedings, 2025)
Olive oil contains a wide range of essential nutrients and bioactive compounds that contribute to its recognized health-promoting properties. Its regular intake has been consistently associated with a reduced risk of cardiovascular diseases and other chronic health conditions. These beneficial effects are primarily attributed to its rich composition of monounsaturated fatty acids, antioxidant phytochemicals, vitamins, and minerals. This study aimed to assess mothers' knowledge regarding the medical uses and health benefits of olive oil. A structured questionnaire was administered to a sample of 82 mothers, including both employed mothers and housewives, residing in Benghazi, Libya. The questionnaire comprised 26 indicators designed to evaluate participants’ awareness of olive oil’s therapeutic applications, appropriate methods of use, potential interactions with medications, and its perceived benefits in conditions such as indigestion, joint inflammation and pain, diabetes, and dyslipidemia. Results showed varied levels of knowledge, significantly associated with age and education. Most participants (82.9%) were employed. Nearly half (48.8%) considered herbal medicine a form of alternative treatment. About 51.2% believed olive oil helps manage central nervous system disorders such as nerve pain and headaches. Only 12.2% acknowledged potential side effects. Moreover, 57.8% reported benefits for chronic illnesses, including diabetes, rheumatoid arthritis, and hypertension. Less than half (43.9%) believed olive oil is suitable for everyone. However, 81.7% recommended its use for hypertension and cholesterol regulation.